2022
DOI: 10.29240/jba.v6i1.3242
|View full text |Cite
|
Sign up to set email alerts
|

Tathwir Mawad al-Ta’bir al-Tahriry ‘Ala Dhuí Maharat al-Tafkir al-Úlya li Tarqiyah Kitabah al-Maqalah li Thullabah Qism Ta’lim al-Lughah al-Árabiyyah

Abstract: The process of developing  learning material  is very important in language education, and that learning materials should be adapted to the progress and demands of time.This paper aims to develop the material learning of arabic writing for Student of Department of Arabic Language University of Muhammadiyah Malang, this paper used Bolito and Julie model, and the data was collected through interview, observation, documents, questionnaire, and pre test  and post test, the technique of data analysis using Miles, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Muhtia et al (2018) conducted the first research on the introduction of blended learning in the literature under the title "Investigating Blended Learning in a Paragraph Writing Course to Promote Student Engagement." Data were collected through interviews, document analysis, observations, and analysis using the interactive model (Miles et al, 2014;Tarmizi et al, 2022). It was revealed that the educational methods in the course centred on the advantages of face-to-face learning as the primary teaching tool.…”
Section: Studies On the Blended Learningmentioning
confidence: 99%
“…Muhtia et al (2018) conducted the first research on the introduction of blended learning in the literature under the title "Investigating Blended Learning in a Paragraph Writing Course to Promote Student Engagement." Data were collected through interviews, document analysis, observations, and analysis using the interactive model (Miles et al, 2014;Tarmizi et al, 2022). It was revealed that the educational methods in the course centred on the advantages of face-to-face learning as the primary teaching tool.…”
Section: Studies On the Blended Learningmentioning
confidence: 99%